2018
DOI: 10.1111/dth.12760
|View full text |Cite
|
Sign up to set email alerts
|

Secondary failure of TNF-α inhibitors in clinical practice

Abstract: Tumor necrosis factor alpha (TNF-α) is a leading inflammatory cytokine that plays a pivotal role in the pathogenesis of psoriasis. In case of a severe course of psoriasis and moderate-to-severe disease in which traditional systemic treatments are ineffective or contraindicated, TNF-α inhibitors (iTNF-α) are used. This class of drugs includes monoclonal antibodies and a fusion protein (etanercept) and can induce a humoral or cell-mediated immune response, leading to formation of antidrug antibodies (ADAs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…In case of secondary failure, one should follow the algorithm as shown in Figure 3 to rule out the other causes. [ 15 20 45 46 ] The expert recommendations on the above-mentioned issues were based on their clinical experience and literature review [ Table 3 ].…”
Section: Therapeutic Approaches and Current Treatment Challenges With Biologicsmentioning
confidence: 99%
“…In case of secondary failure, one should follow the algorithm as shown in Figure 3 to rule out the other causes. [ 15 20 45 46 ] The expert recommendations on the above-mentioned issues were based on their clinical experience and literature review [ Table 3 ].…”
Section: Therapeutic Approaches and Current Treatment Challenges With Biologicsmentioning
confidence: 99%
“…In a single patient we can find various types of anti-IFX and anti-ADA Abs that target various regions of the same therapeutic drug. In such case the amount of free drug molecules that have remained capable of binding TNF-α may be significantly diminished, which brings about a change in the drug pharmacokinetics and pharmacodynamics [9]. Despite this matter is still debating, a recent work by Van Schie et al [10] demonstrated that anti drugantibodies only target idiotype.…”
Section: Anti-infliximab and Anti-adalimumab Antibodiesmentioning
confidence: 99%
“…Furthermore, neutralizing anti-IFX Abs may increase the risk of HSRs during IFX infusion and IgG-mediated anti-IFX Abs may cause an IgE-independent anaphylactic reaction by activating the complement system. Other adverse effects stemming from the formation of immune complexes include serum sickness, Arthus reaction, bronchoconstriction, or thromboembolic events [9]. However, Verstockt et al [20] analyzed samples from 116 biologically naive CD patients with active disease and confirmed that early monitoring of ADA serum levels to guide dose optimisation may prevent immunogenicity and influence long-term outcome.…”
Section: Anti-infliximab and Anti-adalimumab Antibodiesmentioning
confidence: 99%
“…Although biologics-based therapeutic approaches show significantly improved outcomes 4 , up to 50% of patients treated with the TNF-α blocking chimeric monoclonal IgG Infliximab face primary failure, due to unresponsiveness of treatment or secondary failure as therapy efficacy is lost over time 1 , 5 . Indeed, Anti-Drug Antibodies (ADAbs) formation, as a consequence of biologics immunogenicity, has been associated with treatment failure and adverse effects, such as hypersensitivity reactions 6 .…”
Section: Introductionmentioning
confidence: 99%